Rancangan Aplikasi Seleksi Atlet Taekwondo Menggunakan Framework Codeigniter Dengan Metode TOPSIS - Tirta Dwi Budiarto (STMIK Budi Darma, 2019)
Taekwondo is one of the sports in martial arts originating from Korea. Someone who wants to take part in a taekwondo competition usually has to take part in the selection held. The selection process in determining the selection of taekwondo athletes is still having problems. In the field there are still obstacles in the selection of athletes caused by systems that still use manual or conventional methods. Apart from that decision making cannot see the criteria in achievement together. The shortcomings in the athlete selection process are the existence of fraudulent selection of trained athletes, as well as the slow process of determining the assessment of selected athletes. To solve the problem, a decision support system is designed to increase the effectiveness of decision making and produce optimal decisions. In this decision support system the method that can be used is the TOPSIS method. Assessment criteria used as a reference for assessment are technique, tactics, mental, physical, age, reflexes and flexibility. The criteria will be a reference for obtaining the final score.